Six Sigma Approach and Examples from Healthcare Organizations - Deniz, Serkan; Çimen, Mesut (Acıbadem Mehmet Ali Aydınlar Üniversitesi, 2017)
ABSTRACT The need for scientific studies focusing on obtaining efficiency in healthcare services, using resources accurately, increasing patient satisfaction, and preventing waste and instability has been increasing due to the financial crises in the sector and the changes in patient expectations. One of the instruments that can be used in the healthcare sector to solve these problems is Six Sigma approach. In this study, the definition and the importance of Six Sigma approach, methodologies used in Six Sigma, Six Sigma roles and responsibilities, and examples related to Six Sigma implementations in healthcare organizations are discussed.